Descripción etológica de la araña roja del cultivo de rosa (rosa sp) en laboratorio. ceasa, sector Salache, provincia de Cotopaxi 2015 - Guerrero Gómez, María Fernanda (2015)
This present research was conducted in the laboratory of Entomology at Technical University of Cotopaxi. In cultivation of roses, so it reports Tetranychus urticae as one of the most important pests; its symptoms are yellowing of leaves and when dwarfism and death of the plant, this pest causes huge economic losses to growers, for this reason, the theme was developed; " ethological description of the red spider in the laboratory rose cultivation ( Rosa sp. ). CEASA, Salache neighborhood Cotopaxi Province 2015 ", this research was conducted to know the life cycle of the pest; observing the specific characteristics for each stage and identify the specie of the pests, descriptive - analytic method with observation techniques and data. Infested leaves was collected with the plague; ethology description Spider began with 5 couples in the adult stage which were given laboratory conditions (temperature: 21 ° C and humidity: 24.8%) in brood chambers, each pair was placed in their respective chamber which had some eggs with spherical shape and bright whitish they were in this state for 5 days, the larvae had the following features: colorless and transparent color with two distinct black spots on the back with three pairs of legs having an average of 5 days at this state in the nymph´s stage that lasted 9 days, also they showed sexual dimorphism for females (deutonymph)….